2019
DOI: 10.1109/jphot.2019.2900994
|View full text |Cite
|
Sign up to set email alerts
|

256 Gb/s Four-Channel SDM-Based PAM4 FSO-UWOC Convergent System

Abstract: Given the rising demand for free-space with underwater environmental monitoring, calamity precaution, and developed industry applications, a free-space optical (FSO)-underwater wireless optical communication (UWOC) convergence is constructed to be an attractive architecture for affording a high transmission capacity. A 256-Gb/s four-channel space-division-multiplexing (SDM)-based four-level pulse-amplitude modulation (PAM4) FSO-UWOC convergent system that exploits two-stage injection-locked red-light vertical-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Our previous study demonstrated a 256-Gb/s four-channel space-division-multiplexing (SDM)-based PAM4 FSO-UWOC integrated system [5]. The 50 m free-space transmission in our previous work is much shorter than the associated value of 500 m operated in this proposal.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…Our previous study demonstrated a 256-Gb/s four-channel space-division-multiplexing (SDM)-based PAM4 FSO-UWOC integrated system [5]. The 50 m free-space transmission in our previous work is much shorter than the associated value of 500 m operated in this proposal.…”
Section: Introductionmentioning
confidence: 76%
“…Owing to the fast evolution of FSO-UWOC integrated systems, they can deliver some tens gigabit data rate over a free-space link with an underwater channel [5]- [7]. With the rising demands for FSO-UWOC integration, constructing a high-speed FSO-UWOC integrated system with long-range transmission (as illustrated Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Given the characteristics of FSO communication and UWLT system, they can provide high transmission rate over a free-space transmission with an underwater link. With the rapid progress of FSO communication and UWLT system, constructing a high-speed FSO-UWLT convergence is vitally important 12 , 13 . In an actual scenario, no UWLT system passes through the air–water–air interface as the laser beam should flee or enter from the top of the water 14 , 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Free-space optical (FSO)-underwater wireless optical communication (UWOC) convergent system is a promising one to conquer the connectivity difficulties [1]- [4]. It is an attractive convergence that has a number of advantages, such as license-free propagation, reuse of atmospherical/underwater operating bandwidths, high directionality, and no electromagnetic interference.…”
Section: Introductionmentioning
confidence: 99%
“…With the implementation of doublet lenses in FSO communications [19]- [21] and laser beam reducer/expander in UWOC links, excellent bit error rate (BER) performance and accepted PAM4 eye diagrams are attained in such demonstrated FSO-UWOC convergent system. Our former work built a 256-Gb/s PAM4 FSO-UWOC convergent system with a four-channel space-division-multiplexing (SDM) scheme [1]. However, four sets of doublet lenses are envisioned to build such complex and costly four-channel SDM FSO-UWOC convergent system.…”
Section: Introductionmentioning
confidence: 99%